Cost and Technical Efficiency of German Hospitals – A Stochastic Frontier Analysis - Annika Frohloff (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Using a newly available and multifaceted dataset provided by the German Federal Statistical Office, this paper is the first to investigate both technical and cost efficiency of more than 1500 German general hospitals conducting a stochastic frontier analysis. The empirical results for the years from 2000 to 2003 indicate that private and non-profit hospitals are on average less cost and technical efficient than publicly owned hospitals. One explanation for this result may be that German private and non-profit hospitals produce at a longer average length of stay and, thereby, a higher cost per case than public institutions due to the incentives provided by reimbursement schemes until 2004. Furthermore, the paper reveals that non-subsidised hospitals are less efficient than their respective counterparts. Controlling for patients' characteristics (in addition to the constructed case-mix weights), it can be shown that a high ratio of old patients decreases efficiency whereas a high ratio of female patients and a high surgery rate increase it.
Keywords: C13; I11; L33; 330; Hospital efficiency; ownership; privatisation; Krankenhaus; Krankenhauskosten; Technische Effizienz; Eigentümerstruktur; Schätzung; Deutschland